Hydrochemical and Hydroacoustic Investigation of the Yugama Acid Crater Lake, Kusatsu-Shirane, Japan - Hernández, Pedro A.; Nogami, Kenji; Padrón, Eleazar; Somoza, Luis; Amonte, Cecilia; Mori, Toshiya; Melián, Gladys V.; Sumino, Hirochicka; Kikawada, Yoshikazu; Pérez, Nemesio M. (Frontiers in Earth Science, 2021)
The gases dissolved in the waters of volcanic lakes can present a serious hazard if the physical-chemical conditions change due to variations in the supply of magmatic gases. The monitoring of gases such as CO2 and He help us understand the degassing process and their connection with magmatic/hydrothermal system. One of the most acidic volcanic lakes on the planet is the Yugama, on Kusatsu Shirane volcano (Japan). We report the results of an interdisciplinary study carried out in August 2013 at Yugama consisting of the first estimation of rate of diffuse CO2 emission, the chemical and isotopic analysis of water and dissolved gases in samples from vertical lake profiles, and an echo-sounding survey. The lake water has an average temperature of 24-25°C, pH 1.01, concentrations of SO42- between 1,227 and 1,654 mgL−1 and Cl− between 1,506 and 2,562 mgL−1, with gas bubbling at several locations and floating sulfur globules with sulfide inclusions. A total of 66 CO2 efflux measurements were taken at the lake surface by means of the floating accumulation chamber method to estimate the diffuse CO2 output from the studied area. CO2 efflux values ranged from 82 up to 25,800 g m−2 d−1. Estimation of the diffuse CO2 emission at Yaguma Crater Lake was 30 ± 12 t d−1. Normalized CO2 emission rate (assuming an area of 0.066 km2) was 454 t km−2 d−1, a value within the range of acid volcanic lakes. Vertical profiles of major ions and dissolved gases showed variations with increases in ion content and dissolved CO2 and He with depth. Acoustic imaging shows the presence of intense bubbling and provides important information on the bathymetry of the lake. The 50–200 kHz echograms exhibit frequent vertical plumes of rising gas bubbles. Within the crater-lake, three circular submarine vents have been identified showing flares due to a significant activity of sublacustrine emissions. This work shows the first data of diffuse CO2 degassing, dissolved gases in water and echosounding (ES) from Yugama Crater Lake. Periodic hydrogeochemical and hydroacoustic surveys at Yugama Crater Lakemay thus help to document changes in the state of activity of this high-risk volcanic area.